Challenges Of Democratization In The Democratic Republic Of Congo (Drc) - YIGZAW, GEDIFEW SEWENET (Universitas Muhammadiyah Yogyakarta, 2019)
The main purpose of this study is to assess the main challenges of democratization in the Democratic Republic of Congo (DRC). In order to enrich the basic information and achieve the intended specific objectives, the study relied upon secondary data sources. Democracy matters for human security in DRC because well-designed and inclusive political institutions and processes are the key to both preventing violence and managing conflict constructively. It is believed that acting for democracy is acting for peace and security. The DRC, which lies in the heart of Africa, is one of the largest and richest mineral resources countries of the continent and has strategic importance for the stability of the Great Lakes region. This study shows that challenges related to a long period of dictatorship, internal conflicts, communal violence, corruption, weak monitoring of weapons, poor leadership, and globalization have affected the democratization processes and indicators of good governance in the DRC. This study recommends that the government of DRC should consolidate democratization and enhance good governance so as to reduce the crises of democracy in the country and thereby collaborative governance with all the local, national, regional and international stakeholders should be established to avoid the long-suffering of the Congolese people.